A New Era of President Prabowo's Leadership and Governance: Indonesia's Food Security - Nirzawan, Fachrizal Dwi; Yudha, Gesit; Wakhid, Ali Abdul (Universitas Islam Negeri Raden Intan Lampung, 2025)
The issue of food security is now an increasingly pressing global concern, particularly amidst the climate crisis, geopolitical instability, and the threat of a global economic slowdown. Countries unable to meet their food needs independently are more vulnerable to dependency and at risk of external pressure. Therefore, this study aims to examine the new direction of food security policy under President Prabowo Subianto's administration as part of a strategy towards national independence, also linked to an Islamic perspective. This research uses a qualitative approach with an exploratory, descriptive-analytical approach. Data collection was conducted through literature review and document analysis. Data were analyzed inductively by classifying and categorizing the information obtained to identify relevant patterns. The analytical technique used was content analysis. The results show that President Prabowo Subianto's leadership offers a new direction in national food security policy through efforts to achieve food self-sufficiency, develop Food Estates, utilize modern agricultural technology, and strengthen cross-sectoral governance. The transformational leadership approach implemented aims to build a long-term vision, strengthen the role of local actors, and improve bureaucratic efficiency. In the context of maqāṣid al-syariah, this policy emphasizes hifz al-nafs and hifz al-mal, so that food security must be based on the principles of justice, sustainability, and public benefit.